Association of recent gay‐related stressful events and emotional distress with suicidal behaviors over 12 months in Chinese men who have sex with men. (21st June 2017) - Yu, Liya; Li, Yanxia; Liu, Li; Li, Shuang; Na, Jun; An, Xiaoxia; Zhou, Yan; Gu, Yuan; Bi, Xuejuan; Mu, Huijuan; Zhang, Rui; Dong, Wen; et al.
Abstract: Introduction: The study was designed to assess the association of gay‐related stressful events (GRSEs) and emotional distress with suicidal behaviors over a 12‐month period in Chinese men who have sex with men (MSM). Methods: A total of 807 MSM were recruited using a respondent‐driven sampling method from 4 cities in northeastern China. The GRSEs were measured using the Gay‐related Stressful Life Events Scale, depression using the Self‐rating Depression Scale, and anxiety using the Self‐rating Anxiety Scale. Results: A total of 26.0% of study participants experienced GRSEs during the 3 months, and their average Self‐rating Depression Scale and Self‐rating Anxiety Scale scores were significantly lower than the national norms. Over a 12‐month period, the prevalence of suicidal ideation, plan, and attempt was 9.7%, 4.0%, and 3.0%, respectively, each of which is at least 3 to 4 times greater than that of male adults in the general population of China. Multiple logistic regression analysis showed that GRSEs significantly increased the risk of suicidal ideation (odds ratio [OR] = 2.3, 95% confidence interval [CI], 1.4‐3.7) and plan (OR = 2.8, 95% CI, 1.3‐6.0). Depressive symptoms significantly increased the risk of suicidal ideation (OR = 3.5, 95% CI, 2.1‐5.8), plan (OR = 4.4, 95% CI, 2.0‐9.6), and attempt (OR = 5.6, 95% CI, 21.94.8). Anxiety symptoms (OR = 3.4, 95% CI, 1.4‐8.4) and cohabitation with a same sex partner (OR = 3.0, 95% CI, 1.2‐7.9) significantly increased the risk of suicide attempt. Discussion: More efforts to reduce GRSE are worth investigating as a strategy to reduce suicidal thoughts and behaviors in Chinese MSM.